Z-O-M-B-I-E-S 2 [videorecording (DVD)] - Manheim, Milo, 2001-; Donnelly, Meg, 2000-; Tordjman, Trevor, 1995-; Russell, Kylee; Jeffery, Carla; Kinney, Chandler, 2000-; Joza, Pearce, 2002- (Walt Disney Home Entertainment, 2020)
Chronicling the continuing adventures of Seabrook High students Addison and Zed, whose budding romance is threatened by the arrival of werewolves.